Nietzsche e la vita eterna nel nostro sé - De Angelis, Massimo (B@belonline, 2021)
Nietzsche’s essential statement is not “God is dead” but “We have killed God”. The almightiness we awarded to our reason has killed Him. We acted this way not only in the modern age but in fact since the middle age. Nietzsche’s struggle hand to hand with Christian heritage is nothing else that a radical criticism of both the whole western civilization and her rationalism. At the place of the almighty thinking subject Nietzsche puts the self as the one that can at the best seek the truth. This ‘integral’ self is also able to set God free from the cage we laid on Him. Nietzsche destroys the old God and at the same time he discovers a new divinity’s space in the human depth. The ‘God inside us’.